Vector mechanics for engineers : - Beer, Ferdinand Pierre (WCB McGraw-Hill, 1997)
Contents: Kinematics of particles; Kinetics of particles: Newton's second law; Kinetics of particles: energy and momentum methods; Systems of particles; Kinematics of rigid bodies; Plane motion of rigid bodies: forces and accelerations...